Proteomic Approaches to Unravel Mechanisms of Antibiotic Resistance and Immune Evasion of Bacterial Pathogens - Torres-Sangiao, Eva; Giddey, Alexander Dyason; Leal Rodriguez, Cristina; Tang, Zhiheng; Liu, Xiaoyun; Soares, Nelson C. (Frontiers in Medicine, 2022)
The pandemic's distress highlights what began in the human field a long time ago: all bacteria, viruses, and parasites continue to be a major threat to human health. In fact, infectious diseases remain the leading cause of death worldwide, with an exponential increase in antibiotic resistance due to a lack of new treatments. In addition to the one common trait, their ability to modulate and escape host immune response. As a result, a challenge in medical microbiology is to develop and apply new experimental approaches that allow for identification of the microbe and its susceptibility profile in a time sensitive manner, as well as their molecular mechanisms of survival and immunomodulation. Over the last three decades, proteomics has contributed to a better understanding of underlying molecular mechanisms operating during microbial drug resistance and pathogenicity. More recently, proteomics has gained new momentum as a result of recent advances in mass spectrometry. Indeed, mass spectrometry-based biomedical research has been made possible in large part by technological advances in instrumentation capability and the continuous improvement of sample processing and workflows. For example, high-throughput applications such as SWATH or Trap ion mobility enable the identification of thousands of proteins in a matter of minutes. This type of in-depth analysis in a short period of time, combined with other supportive high-tech applications like data processing and artificial intelligence, represents an once-in-a-lifetime opportunity to translate knowledge-based findings into measurable impacts like new antimicrobial biomarkers and drug targets.